The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1371/journal.pone.0180816
|View full text |Cite
|
Sign up to set email alerts
|

Serum neutrophil gelatinase-associated lipocalin the estimation of hospital prognosis in patients with ST-elevated myocardial infarction

Abstract: We aimed to assess the clinical significance of serum levels of neutrophil gelatinase-associated lipocalin (sNGAL) for predicting in-hospital outcomes in patients with ST-elevated myocardial infarction (STEMI). Patients admitted within 24 hours of developing STEMI clinical symptoms were evaluated for sNGAL on hospitalization days 1 and 12. Recurrent myocardial infarction, early post-infarction angina, acute cerebrovascular accident, and death were assessed as adverse outcomes during hospitalization. The actors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
(14 reference statements)
1
6
1
2
Order By: Relevance
“…The ROC curve analysis showed that NGAL of more than 190 ng/mL could detect cardiovascular mortality in STMI patients with a sensitivity of 86% and specificity of 77% [ 86 ]. Among 260 STEMI patients admitted within 24 h after onsetting clinical symptoms, plasm NGAL on day 12 could predict combined adverse outcomes, including recurrent myocardial infarction, post-infarction angina, acute cerebrovascular accident, and death [ 87 ]. In another study that included 357 consecutive patients admitted to the hospital within 24 h after onseting STEMI, plasm NGAL level of more than 1.25 ng/mL on the 12th–14th day was associated with a 2.9-fold higher risk of a combined endpoint of cardiovascular death or any cardiovascular complication after 3 years of follow-up [ 88 ].…”
Section: Neutrophil Gelatinase-associated Lipocalin (Ngal)mentioning
confidence: 99%
See 1 more Smart Citation
“…The ROC curve analysis showed that NGAL of more than 190 ng/mL could detect cardiovascular mortality in STMI patients with a sensitivity of 86% and specificity of 77% [ 86 ]. Among 260 STEMI patients admitted within 24 h after onsetting clinical symptoms, plasm NGAL on day 12 could predict combined adverse outcomes, including recurrent myocardial infarction, post-infarction angina, acute cerebrovascular accident, and death [ 87 ]. In another study that included 357 consecutive patients admitted to the hospital within 24 h after onseting STEMI, plasm NGAL level of more than 1.25 ng/mL on the 12th–14th day was associated with a 2.9-fold higher risk of a combined endpoint of cardiovascular death or any cardiovascular complication after 3 years of follow-up [ 88 ].…”
Section: Neutrophil Gelatinase-associated Lipocalin (Ngal)mentioning
confidence: 99%
“…Plasm NGAL on day 12 could predict combined adverse outcomes 2. A marker of MI severity [ 87 ] STEMI patients Plasm NGAL level of more than 1.25 ng/mL on the 12th–14th day was associated with a higher risk of a combined endpoint of cardiovascular death or any cardiovascular complication [ 88 ] ACS patients NGAL concentration could predict long-term mortality [ 89 ] STEMI patients Plasm NGAL level above 2.6 ng/ml on day 12 after onsetting STEMI was related to a fourfold increase of all-cause mortality [ 90 ] STEMI patients STEMI patients in the higher NGAL group presented greater risk of MACEs and all-cause mortality [ 91 ] Cathelicidin diagnostic value Patients or MI mice 1. CRAMP was reduced from I/R mice and oxygen glucose treated cardiomyocytes 2.…”
Section: Arginasementioning
confidence: 99%
“…[15][16][17] A number of studies have also reported associations between elevated NGAL levels and poor outcomes (e.g., mortality, hospital readmissions, heart failure, major adverse cardiac events) in patients with pre-existing CVD or kidney disease. [18][19][20][21][22][23] The overall evidence suggests that NGAL may be involved in CVD development.…”
Section: Introductionmentioning
confidence: 99%
“…[24] The prognostic value of NGAL level at discharge, as an indicator to complement assessments of brain natriuretic peptide, is a strong prognostic indicator of 30 days outcomes in patients admitted for acute heart failure. [13] Barbarash et al [25] and Karetnikova et al [26] found measurement of NGAL level in patients with STEMI on the 12th to 14th day after hospital admission may improve prediction of MI severity and adverse cardiovascular events. A study from Russia found NGAL level above 2.6 ng/mL on 12th day during hospital stay lead to 4 times all-cause mortality during 3-year follow-up.…”
Section: Discussionmentioning
confidence: 99%